Enhanced marine antifouling performance of silver-titania nanotube composites from hydrothermal processing - Yee, M.S.L.; Khiew, P.S.; Lim, S.S.; Chiu, W.S.; Tan, Y.F.; Kok, Y.Y.; Leong, C.O. (Elsevier, 2017)
Marine fouling is an age-old problem which continues to plague the maritime industry. The fouling process progresses from an initial formation of bacterial biofilm on unprotected surfaces. Silver is a well-known antimicrobial agent which is well-tolerated by mammals, while titania nanotubes have enhanced properties due to a greater specific surface area on the inner and outer surfaces of the tubular structure. A novel 2-step hydrothermal synthesis of a silver-titania nanotube (Ag/TNT) composite material is presented. The morphology, particle size, chemical content, crystal structure, optical properties and surface area were systematically characterized. Determination of biofilm inhibitory properties revealed that Ag/TNT with the lowest silver content (0.95 wt% Ag) decorated with Ag nanoparticles of ca. 3 nm reduced biofilm formation of marine bacterium Halomonas pacifica by 98% compared to pure titania nanotubes and bulk silver alone. Growth inhibition of marine microalgae Dunaliella tertiolecta and Isochrysis sp. were also observed.